SISTEM ISPO UNTUK MENJAWAB TANTANGAN DALAM PEMBANGUNAN KELAPA SAWIT INDONESIA YANG BERKELANJUTAN - Ermanto Fahamsyah; Eusebius Pantja Pramudya (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2017)
The implementation of ISPO certification system which has been running since 2011 in addition to having experienced various achievements and developments also encountered various obstacles, problems, challenges and demands. The formulation of the problems analyzed and answered in this study are: what aspects should be formulated in order to strengthen ISPO system? To analyze and answer the problem formulation is used framework thinking about legal system theory or Legal System Theory developed by Lawrence M. Friedman. The research method used in this study is more focused on normative legal research. Based on the analysis, it can be concluded that the aspects that must be formulated in order to strengthen ISPO system include: First, related to the aspect of law substance, ISPO system arrangement must be increased from the level of Minister of Agriculture Regulation to the level of Presidential Regulation. Through this Presidential Regulation is expected to become a stronger legal umbrella in the implementation of ISPO system. Second, in relation to aspects of its legal apparatus, the institutional mechanisms of ISPO certification shall be enhanced and strengthened. Third, from the legal culture aspect, there must be a common understanding about the definition and concept of sustainability in the management and development of oil palm Indonesia.Keywords: ISPO, Development, Palm Oil, Sustainable, Indonesia ABSTRAKPenyelenggaraan sistem sertifikasi ISPO yang berjalan sejak 2011, di samping telah mengalami berbagai pencapaian dan perkembangan, menemui berbagai hambatan, masalah, tantangan, dan tuntutan. Penelitian ini bertujuan untuk melihat aspek-aspek apa saja yang harus dirumuskan dalam rangka penguatan sistem ISPO? Untuk menganalisis dan menjawab rumusan masalah tersebut, digunakan kerangka berpikir tentang teori sistem hukum atau legal system theory yang dikembangkan oleh Lawrence M. Friedman. Metode penelitian yang digunakan dalam kajian ini lebih dititikberatkan pada penelitian hukum normatif. Berdasarkan pada analisis yang dilakukan, dapat disimpulkan bahwa aspek-aspek yang harus dirumuskan dalam rangka penguatan sistem ISPO meliputi: pertama, terkait dengan aspek substansi hukum, pengaturan sistem ISPO harus ditingkatkan dari tingkat peraturan menteri pertanian menjadi tingkat peraturan presiden. Peraturan presiden ini diharapkan dapat menjadi payung hukum yang lebih kuat dalam penyelenggaraan sistem ISPO. Kedua, terkait dengan aspek aparatur hukumnya, mekanisme kelembagaan penyelenggaraan sertifikasi ISPO harus disempurnakan dan dikuatkan. Ketiga, dari aspek budaya hukum, harus ada persamaan pemahaman mengenai definisi dan konsep sustainability dalam pengelolaan dan pengembangan kelapa sawit Indonesia.Kata kunci: ISPO, Pembangunan, Kelapa Sawit, Berkelanjutan, Indonesia